PTH-125 BSG VS UEG – Which Annual Meeting has The Highest Conversion Rate of Abstracts to Full Publication?. (17th August 2016) - Kurien, M; Hopper, AD; Akram, R; Glover, R; Issa, A; Peever, E; Purves, J; Scanu, E; Sanders, DS
Abstract : Introduction: Abstract presentations at scientific meetings allow rapid dissemination of novel research and enables peer review before submission for publication. The percentage of abstracts that achieve full publication, however is variable ranging between 11–78% from other medical specialty meetings. This study evaluates the conversion rate of abstracts presented at the BSG annual meeting, and comperes the outcome from this national meeting with another internationally recognised gastrointestinal meeting (UEGW). Methods: All abstracts presented at the BSG between 1994 and 2008 were reviewed in Nov 2012. UEGW meeting abstracts between 2009 and 2011 were reviewed in October 2014. Review dates for both the BSG and UEGW abstracts were at least 3 years post the last meeting evaluated, which is a previously reported upper limit timescale for subsequent full publication. PUBMED and EMBASE databases were reviewed using cross-referencing of first author, senior author and at least one key word from the abstract title. Abstracts and possible full publications were then examined in tandem to ensure they represented the same study. Abstracts that were withdrawn were excluded from the study. In addition to publication rates, data was collected on lag time to publication and journal impact factors. Statistical analyses were performed using contingency tables and chi squared statistics for categorical data using SPSS version 20.0. Results: Over a 15 year period (1994–2008) the conversion rate of BSG abstracts to full publication was 33.4% (2273/6798, mean impact factor of published journal = 3.8). The mean lag time until publication was 23 months, with service development abstracts having the lowest conversion rate of 6.9% (8/116). Of the 6560 abstracts presented at UEGW meetings between 2009–2011, 31.0% (2033/6560) went on to full publication in indexed journals (mean impact factor = 3.93). The mean lag time between UEG abstract presentation and full publication was 16 months. The conversion rate of BSG abstracts is broadly comparable to UEGW, however it did achieve a statistically significant difference (33.4% vs.31.0% p = 0.003). Conclusion: This study demonstrates that the BSG compares favourably to another internationally recognised gastroenterology meeting with regards to the outcomes of its abstracts. Findings from this work provides reassurances to researchers that submission to the BSG annual meeting is worthwhile, and that the peer-review process provided increases the likelihood of success in achieving subsequent full publication. Disclosure of Interest: None Declared